Pengaruh Penggunaan Gawai terhadap Pemerolehan Bahasa Anak Usia - Zakaria, Ulfa; `Ismail , Lifka (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2022)
Early childhood language acquisition cannot be separated from the use of gadgets. Today's technology is so sophisticated that on devices there are applications that provide entertainment that is popular with young children. Language acquisition is the process of gaining the ability to capture, produce and use the languages one hears. The research method used is a qualitative descriptive method which provides an overview of the research results. In addition, data collection methods and data analysis techniques were carried out. The research results show that young children acquire languages easily through devices. Young children get this through watching shows on their devices. They are able to imitate the languages they hear. It is very easy for them to remember what is presented in the image display. The use of gadgets has both positive and negative impacts. The conclusion from this research is that monitoring and limiting the use of gadgets for young children is very important. Otherwise, it will have an impact on the child's language acquisition.